Global Financial Stability Report, October 2018 : A Decade after the Global Financial Crisis: Are We Safer?. (Global Financial Stability Report; Global Financial Stability Report ;, 2018)
In the 10 years since the global financial crisis, regulatory frameworks have been enhanced and the banking system has become stronger, but new vulnerabilities have emerged, and the resilience of the global financial system has yet to be tested.